Peningkatan Prevensi Masalah Psikososial Pasca Bencana dengan Group Supportive Therapy dan Play Therapy - Zolla Amely Ilda; Renidyati Renidyati; N. Rachmadanur; Sunardi Sunardi; Verra Widhi Astuti; Widdefrita Widdefrita (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
West Sumatra is one of the disaster-prone areas in Indonesia, due to geographical, climatic, geological and other factors. Padang Pariaman is one area that is often affected by disasters, especially earthquakes. One of the vulnerable groups directly affected by the disaster is school-age children. Psychological problems in school-age children can affect life in the future. This area-based community service activity aims to increase independence, increase health status and community welfare by increasing the ability of school-age children to reduce the prevention of post-disaster psychosocial problems through group supportive therapy and Play Therapy. The target of this activity is school-age children and teachers, totaling 37 people. This activity is carried out from May to November 2021 in Padang Pariaman. The method of activity is education and simulation divided into three stages: (1) planning stage, (2) implementation stage, (3) evaluation stage. There is an increase in the understanding and skills of the community, especially school-age children in the prevention of post-disaster psychosocial problems, as well as an increase in the network of collaboration between the Health Polytechnic, the Ministry of Health of Padang and the District Government of Padang Pariaman.